Impact of simplified therapeutic guidelines on antibiotic prescriptions: a prospective multicentre comparative study. (18th December 2019) - Roger, Pierre-Marie; Peyraud, Ingrid; Vitris, Michel; Romain, Valérie; Bestman, Laura; Blondel, Lionel; Gras, Hélène; Hauchart, Christine; Morandi, Véronique; Rancezot, Agnès; Borredon, Gaelle; Dautezac, Véronique
Abstract: Objectives: We studied the impact of simplified therapeutic guidelines (STGs) associated with accompanied self-antibiotic reassessment (ASAR) on antibiotic use. Methods: Prospective antibiotic audits and feedback took place at 15 hospitals for 12 months, allowing STGs with ≤15 drugs to be devised. STGs were explained to prescribers through sessions referred to as ASAR. Optimal therapy was defined by the conjunction of a diagnosis and the drug specified in the STGs. Analysis of consumption focused on critical drugs: amoxicillin/clavulanic acid, third-generation cephalosporins and fluoroquinolones. Results: We compared prescriptions in five hospitals before ( n = 179) and after ( n = 168) the implementation of STGs + ASAR. These tools were associated with optimal therapies and amoxicillin/clavulanic acid prescriptions [adjusted odds ratio (AOR) 3.28, 95% CI 1.82–5.92 and 2.18, 95% CI 1.38–3.44, respectively] and fewer prescriptions for urine colonization [AOR 0.20 (95% CI 0.06–0.61)]. Comparison of prescriptions ( n = 1221) from 10 departments of three clinics with STGs + ASAR for the first quarters of 2018 and 2019 revealed that the prescriptions by 23 ASAR participants more often complied with STGs than those by 28 other doctors (71% versus 60%, P = 0.003). STGs alone were adopted by 10 clinics; comparing the prescriptions ( n = 311) with the 5 clinics with both tools, we observed fewer unnecessary therapies in the latter [AOR 0.52 (95% CI 0.34–0.80)]. The variation in critical antibiotic consumption between 2017 and 2018 was −16% for the 5 clinics with both tools and +20% for the other 10 ( P = 0.020). Conclusions: STGs + ASAR promote optimal antibiotic therapy and reduce antibiotic use.